Strong Stability Preserving Runge-Kutta Methods Applied to Water Hammer Problem - Santiago, D. F. G.; Antunis, A. F.; Trindade, D. R.; Brandão, W. J. S. (Trends in Computational and Applied Mathematics, 2022)
The characteristic method of lines is the most used numerical method applied to the water hammer problem. It transforms a system of partial differential equations involving the independent variables time and space in two ordinary differential equations along the characteristics curves and then solve it numerically. This approach, although showing great stability and quick execution time, creates ∆x-∆t dependency to properly model the phenomenon. In this article we test a different approach, using the method of lines in the usual form, without the characteristics curves and then applying strong stability preserving Runge-Kutta Methods aiming to get stability with greater ∆t.